A Patient With Chronic Cough And Fever: A Case Of Extensive Sarcoidosis; A Notorious Mimicker Of Tuberculosis - Pandey, Parishrut Prasad; Gupta, Prabind; Koirala, Achyoot Sharan; Yadav, Rishikesh (Journal of Bharatpur Hospital, 2026)
Background: Sarcoidosis is a chronic systemic granulomatous disease that closely mimics tuberculosis (TB) in clinical, radiological, and histopathological features. In TB-endemic regions like Nepal, this overlap frequently leads to misdiagnosis and delayed appropriate treatment.Case Presentation: A 53-year-old male construction worker from India presented with 8–9 months of intermittent cough, low-grade fever, mild chest pain, and exertional dyspnea (MMRC Grade II). He had a history of TB contact and had already completed 8 months of anti-tubercular therapy (ATT) with incomplete and transient improvement. Investigations showed elevated ESR, negative sputum Gene Xpert, negative Mantoux test, and restrictive pattern on spirometry. CT chest revealed bilateral consolidation, fibrotic bands, fine nodules, and ground glass opacities. Bronchoscopy with BAL showed airway inflammation and an elevated CD4:CD8 ratio. CT-guided lung biopsy confirmed non-caseating granulomas with extensive fibrosis, establishing a diagnosis of pulmonary sarcoidosis (Scadding Stage IV). The patient responded well to pulse methylprednisolone followed by oral prednisolone, with significant symptomatic improvement at two-week follow-up.Conclusion: This case underscores the need to maintain sarcoidosis as an active differential diagnosis in TB-endemic settings, particularly when clinical response to ATT is suboptimal. Histopathological confirmation remains essential to avoid prolonged, inappropriate treatment